2013 World Ocean Atlas Aids High‐Resolution Climate Studies. Issue 41 (14th October 2014) - Boyer, Tim P.; Garcia, Hernan E.; Locarnini, Ricardo A.; Zweng, Melissa M.; Mishonov, Alexey V.; Reagan, James R.; Antonov, John I.; Baranova, Olga K.; Biddle, Mathew M.; Johnson, Daphne R.; Paver, Christopher R.
<x xml:space="preserve">Abstract</x> Since 1982, the Levitus Climatological Atlas of the World's Ocean and each succeeding World Ocean Atlas have been used to provide initial and boundary conditions for modeling studies, as well as baselines for climate studies. However, there has been a broadening demand for ocean modeling on spatial scales finer than 1‐degree resolution [e.g., Penduff et al., 2010]. Likewise, vertical resolution for isobaric coordinate models is important for realistic representation of ocean processes [Wang et al., 2008].